Properties of spray-dried iron microcapsule using hydrolysed glucomannan as encapsulant: effect of feed viscosity - Wardhani, Dyah Hesti; Wardana, Irsyadia Nindya; Ulya, Hana Nikma; Kumoro, Andri Cahyo; Aryanti, Nita (Penerbit Universiti Kebangsaan Malaysia, 2023)
As one of the polysaccharides with high viscosity, even in low concentration, glucomannan could block the nozzle and hinder its application as spray-dried encapsulant. The present research aimed to investigate the effect of viscosity of hydrolysed glucomannan as a spray-dryer feed on properties of encapsulated iron particles. Glucomannan was hydrolysed using cellulase to obtain various viscosities (83-222 cP) and used for encapsulating iron. Enzymatic hydrolysis reduced the glucomannan’s glass transition temperature and transmittance values of O-H, C-O, and C-H groups. Increasing the viscosity lightened the particle colour, and improved encapsulation efficiency and mean particle diameter, however, reduced moisture content and bulk density. The highest encapsulation efficiency (99.95%) was obtained using the most viscous encapsulant (222 cP). Thicker encapsulants produced larger particles with more wrinkles on the surface but performed better in protecting iron. Solubility and swelling of the particles were higher in neutral solution (pH=6.8) than in an acidic one. The degree of iron degradation was around 70% after 10 months of storage. These results suggested the use of an appropriate viscosity of hydrolysed glucomannan not only allow it to be sprayed but also showed a potency to protect the iron from solubility in acid ambient and degradation during the storage.